Synthesis of antiulcer drug esomeprazole - Giap, Tran Huu; Tung, To Hai; My Hue, Van Thi; Hue, Cao Thi; Minh Hang, Nguyen Thi; Minh, Chau Van; Thanh, Le Nguyen (Vietnam Journal of Chemistry, 2015)
Esomeprazole (Nexium®), the (S)-isomer of Omeprazole, is the first proton-pump inhibitor developed as a single isomer for the treatment of acid-related diseases. It is used for the treatment of peptic ulcers, gastroesophagal reflux disease, and erosive esophagitis. Herein, we report our synthetic study of esomeprazole sodium salt from the starting    2-mercapto-5-methoxybenzimidazole and 2-(chloromethyl)-4-methoxy-3,5-dimethylpyridine hydrochloride reagents. The Esomeprazole sodium salt was obtained from enantioselectivesulfoxidation reaction in moderate yield with high enantioselectivity.